2014
DOI: 10.1007/s10886-014-0433-1
|View full text |Cite
|
Sign up to set email alerts
|

Putative Pathway of Sex Pheromone Biosynthesis and Degradation by Expression Patterns of Genes Identified from Female Pheromone Gland and Adult Antenna of Sesamia inferens (Walker)

Abstract: The general pathway of biosynthesis and degradation for Type-I sex pheromones in moths is well established, but some genes involved in this pathway remain to be characterized. The purple stem borer, Sesamia inferens, employs a pheromone blend containing components with three different terminal functional groups (Z11-16:OAc, Z11-16:OH, and Z11-16:Ald) of Type-I sex pheromones. Thus, it provides a good model to study the diversity of genes involved in pheromone biosynthesis and degradation pathways. By analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 54 publications
4
39
0
Order By: Relevance
“…Unfortunately, we did not find an AO from the transcriptomic database, similar as studies with sex pheromone gland transcriptome analysis in other species using aldehyde(s) as sex pheromone component(s), such as H. virescens 47, Agrotis segetum 17 and A. ipsilon 48. In Sesamia inferens , 1 AO was found with very low expression level in the sex pheromone gland transcriptome49. Therefore, more sensitive approaches are needed to identify the possible AO genes in moths.…”
Section: Discussionsupporting
confidence: 75%
“…Unfortunately, we did not find an AO from the transcriptomic database, similar as studies with sex pheromone gland transcriptome analysis in other species using aldehyde(s) as sex pheromone component(s), such as H. virescens 47, Agrotis segetum 17 and A. ipsilon 48. In Sesamia inferens , 1 AO was found with very low expression level in the sex pheromone gland transcriptome49. Therefore, more sensitive approaches are needed to identify the possible AO genes in moths.…”
Section: Discussionsupporting
confidence: 75%
“…Labeling studies demonstrated that palmitic acid (C16) and stearic acid (C18) are the FAS products in most moth PGs [15,[66][67]. Herein, we identified five FASs with lengths ranging from 301 bp to 8170 bp in the S. insularis PG transcriptome (Table 2 and S1 Text), These results are similar to those reported for other insects, with six and three FASs in A. segetum [58] and Sesamia inferens [68], respectively. Among the five FASs, only SinsFAS2 has an intact ORF.…”
Section: Fatty Acid Synthase (Fas)supporting
confidence: 87%
“…Previously, these studies have mostly been focused on model species with sequenced genome available, such as Drosophila melanogaster, Bombyx mori, Aphis gossypii and several other insect species [ 17 22 ]. With the development of the next generation sequencing (NGS) techniques, numerous chemosensory genes have been identified from various insect species, such as Manduca sexta [ 23 ], Helicoverpa armigera [ 24 ], Cydia pomonella [ 25 ], Spodoptera littoralis [ 26 28 ], Sesamia inferens [ 29 ], Chilo suppressalis [ 30 ] and Aphis gossypii [ 31 ], etc.…”
Section: Introductionmentioning
confidence: 99%